Studi Deskripstif Kuantitatif Fenomena Perilaku Penonton Drama Korea di Kalangan Mahasiswa Universitas Sumatera Utara - Sarah Bonova Bere Sinaga; Dewi Kurniawati (Peneliti.net, 2023)
This research is entitled “Quantitative Descriptive Study of the Behavior Phenomenon of Korean Drama Audience Among North Sumatra University Students”. The purpose of this study was to determine the characteristics and behavioral phenomena of Korean drama audience among students Universitas Sumatera Utara. The theory used in this research is Theory of Reasoned and Action. This study uses a descriptive study, which only describes situations and events, does not test hypotheses or make predictions. The population in this study were active students at the University of North Sumatra, amounting to 41,962 people. The sample was determined using the Taro Yamane formula and a sample of 100 people was obtained. The sampling technique in this study was purposive sampling. Data collection technique using questionnaires. The data analysis technique used was single table analysis using Statistical Product and System Solution (SPSS) version 26.0. Based on the results of the study, the characteristics of the respondents in this study were mostly female with a total of 87 respondents with a percentage of 87%. The results showed as many as 77% of Korean drama audience students stated that they strongly agreed to watch Korean dramas because of the varied genres but as many as 63% of viewers chose not to follow Korean trends after watching Korean drama(s). The results of the cross table research between the frequency of watching Korean dramas in a week with the Korean drama genre being more varied compared to other dramas obtained the most results at a frequency of 2x a week with a total of 25 respondents.